14th St. Gallen International Breast Cancer Conference 2015: Evidence, Controversies, Consensus - Primary Therapy of Early Breast Cancer: Opinions Expressed by German Experts - Jackisch, Christian; Harbeck, Nadia; Huober, Jens; Von Minckwitz, Gunter; Gerber, Bernd; Kreipe, Hans-Heinrich; Liedtke, Cornelia; Marschner, Norbert; Moebus, Volker; Scheithauer, Heike; Schneeweiss, Andreas; Thomssen, Christoph; et al. (Breast Care, 2015)
The key topics of this year's 14th St. Gallen Consensus Conference on the diagnosis and therapy of primary breast cancer were again questions about breast surgery and axillary surgery, radio-oncology and systemic therapy options in consideration of tumor biology, and the clinical application of multigene assays. This year, the consensus conference took place in Vienna. From a German perspective, it makes sense to substantiate the results of the vote of the international panel representing 19 countries in light of the updated national therapy recommendations of the AGO (Arbeitsgemeinschaft Gynäkologische Onkologie). Therefore, 14 German breast cancer experts, 3 of whom are members of the International St. Gallen Panel, have commented on the voting results of the St. Gallen Consensus Conference 2015 in relation to clinical routine in Germany.
EVALuna2:17563